Comparative Analysis of Glucosinolate and Phenolic Compounds in Green and Red Kimchi Cabbage (Brassica rapa L. ssp. pekinensis) Hairy Roots after Exposure to Light and Dark Conditions - Sook Young Lee; Haejin Kwon; Jae Kwang Kim; Chang Ha Park; Ramaraj Sathasivam; Sang Un Park (Horticulturae, 2023)
Brassica rapa L. ssp. pekinensis (Lour.) Hanelt (kimchi cabbage) is a major vegetable cultivated in Korea, and its hairy roots (HRs) are rich in glucosinolates and phenolic compounds. This study aimed to induce HRs from cotyledon explants via the transformation of the Agroacterium rhizogenes strain R1000 and examine the glucosinolate and phenolic compounds present in the HRs of two kimchi cabbage (green and red) cultivars after exposure to 16 h light/8 h dark conditions (photosynthetic photon flux density of 54.6 µmol m−2 s−1) and continuous dark conditions. The highest HR production was achieved in the green kimchi cabbage grown under dark conditions (0.37 ± 0.01 DW g/30 mL). The highest glucosinolate and phenolic contents were neoglucobrassicin and catechin hydrate, which were highest in the green kimchi HRs grown under dark (GKHD) conditions (5268.29 ± 292.84 µg/g DW) and green HRs grown under light (GKHL) conditions (203.49 ± 4.70 µg/g DW), respectively. A heat map showed that the red kimchi HRs grown under dark conditions (RKHD) and the GKHL condition accumulated the highest glucosinolate and phenolic contents. Principal component (PCA) and partial least-squares discriminant (PLS-DA) analyses of the 13 identified metabolites showed a clear separation. According to a variable importance in projection (VIP) analysis, quercetin was the most important metabolite, leading to a clear separation. The most suitable conditions for enhancing the glucosinolate and phenolic contents were the GKHD and GKHL conditions, respectively, whereas both compounds were enhanced in the RKHD condition. HRs cultures cultivated under light and dark conditions are a promising method to enhance the production of specific health-promoting bioactive metabolites, which might be helpful in the pharmaceutical and nutraceutical industries.